Analysis of Coliform and Colifecal Contamination on Sanjai Chip Using MPN Method - Asiska Permata Dewi; Konny Putriani (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2022)
Sanjai chip is a type of traditional food made of cassava processing and it is typical food of West Sumatera. Sanjai chips sold at Pasar Bawah in Pekanbaru City sold in an open state and the location is close to the trash heap, so it is feared to be contaminated by bacteria. The purpose of this research was to find out if there was or there was no contamination of coliform and colifecal bacteria on Sanjai chips. This bacteria contamination was analyzed on seven sanjai chip from different sellers using Most Probable Number (MPN) method with type 5-1-1. The result on seven samples obtained shows that all the samples did not contain coliform marked with there was no formation of gas bubble in the durham tube in the preliminary test. Therefore, affirmation test in this research was not continued. Thereby, Sanjai chips sold at Pasar Bawah Pekanbaru City fulfilled the requirement according to Indonesian National Standard (SNI) Number 7388-2009 about maximum limit of microba contamination in food, where the bacteria number allowed is <3/gram, so it is safe for consumption.